Critical historical archaeology - Leone, Mark P. (Left Coast Press, 2010)
How can we use the past to make sense of the issues and problems that concern us in the present? Mark Leone, the leading critical theorist in historical archaeology, urges archaeologists to view their discipline as an activist pursuit. This volume is partly his autobiographical reflection on a thirty five year career, part a collection of Leone's classic writings on Annapolis, Williamsburg, Shakertown, St. Mary's, and other key sites, and part a synthesis of his current thinking on how historical archaeology can engage the cultural and political issues of our time. Critical Historical Archaeology is an important summary of the work and thinking of one of our most thoughtful, influential archaeologists. -- Book Jacket.